Accelerated biological aging as a potential mediator mediates the relationship between metabolic syndrome and the risk of psoriasis: a prospective analysis from the UK biobank - Tian, Rongqian; Qiu, Shaona; Zhang, Jinrong; Chen, Ming; Yu, Hai; Lau, Waichi; Lyu, Jun; Deng, Liehua (Frontiers in Immunology, 2025)
BackgroundIncreasing evidence suggests that metabolic syndrome (MetS) may contribute to the development of psoriasis. However, the mediating role of accelerated aging in this association remains unclear.MethodsThis study utilized data from 319,263 participants in the UK Biobank. Cox proportional hazards models were used to assess the associations between MetS, genetic predisposition, and psoriasis risk. Mediation analysis examined the role of accelerated aging (PhenoAgeAccel) in the relationship between MetS, its components, and psoriasis.ResultsMetS was associated with a 30% increased risk of psoriasis (HR: 1.30; 95% CI: 1.20–1.40). Among its components, abdominal obesity, low HDL cholesterol, high triglycerides, and hyperglycemia were each independently linked to higher risk. Individuals with both MetS and high genetic susceptibility had a substantially increased risk (HR: 2.93; 95% CI: 2.51–3.43). PhenoAgeAccel significantly mediated 28.8% of the MetS–psoriasis association.ConclusionsMetS and its components play a key role in psoriasis development, especially in genetically susceptible individuals. Accelerated aging may partially explain this link, suggesting a potential biological pathway and underscoring the importance of early MetS identification.